Profil Suhu Pada Pengomposan Tandan Kosong Sawit Sisa Media Jamur Merang (Volvarielle Volvacea) Dengan Variasi Berat Penambahan POME (Palm Oil Mill Effluent) - Amarullah Amarullah; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The conventional composting technique of oil palm empty bunches takes several months or even a year to reach maturity because it has a high C / N ratio (64.46) and lignin polymer bond (27.60-32.50%) which hard to degrade. Using Merang Mushroom (Volvariella volvacea) as pretreatment before composting is expected to decrease lignin level and accelerate degradation of empty palm bunches. Merang Mushroom (Volvariella volvacea) is one of white rot fungus which able producing enzymes to degrade the lignin structure became simpler. The purpose of this study is determine the profil temperature in composting process of spent mushroom media by addition Palm Oil Mill Effluent (POME).This study was conducted by varying the comparison of TKSJ: POME (1: 0, 2: 1, 1: 1 and 1: 2 w / w) with in vessel composting model. The results showed the temperature in this process reachs standard SNI 19-7030-2004 (28-29 oC). Keywords: Merang Mushroom, POME, C/N and Composting